New lyssomanine and hisponine jumping spiders from Africa (Araneae: Salticidae) - Maddison, Wayne P.; Zhang, J. X. (Zootaxa, 2006)
Three new species of salticid spider from Africa are described and illustrated. These are Goleba lyra, new species, a lyssomanine from Madagascar, Massagris schisma, new species, a hisponine from South Africa, and Tomocyrba andasibe, new species, a hisponine from Madagascar.